Factores relacionados al donante como causa de diferimiento para la donación sanguínea en el Centro Hemodador Regional de Loreto, 2024 - Armas Rengifo, Roger Dante (2025)
The present study aimed to analyze the relationship between donor characteristics and deferral causes in blood donation at the Regional Blood Center of Loreto during 2024. An observational, descriptive, cross-sectional, and retrospective study was conducted based on the analysis of 10,542 donor candidate records. Of the donors, 62.1% were men, and the most frequent age group was 18 to 30 years (53.8%). A total of 3,602 deferrals were recorded (34.2%), with the main causes being hematological conditions (39.0%), reactive screening tests (15.8%), and medication use (7.1%). Hepatitis B was the most frequent infectious marker among positive screenings (57.0%), followed by syphilis (19.2%). Deferral was significantly associated with age, sex, marital status, place of residence, and blood group. Individuals over 50 years had a higher risk of deferral (OR: 1.7; 95% CI: 1.5–2.0). Women showed a higher probability of deferral (OR: 1.9; 95% CI: 1.8–2.1). Those from districts outside urban Iquitos also had an increased risk (OR: 1.7; 95% CI: 1.5–2.1). Blood group A was associated with a higher risk of deferral compared to other groups (OR: 1.5; 95% CI: 1.3–1.8).